THE INFLUENCE OF RGEC ON STOCK RETURN PRIVATE COMMERCIAL BANKS LISTED ON THE INDONESIA STOCK EXCHANGE YEAR PERIOD 2017 – 2021 - Ni Luh Ketut Dewi Aryasari (SEAN Institute, 2022)
The Influence of RGEC on Share Returns of Private Commercial Banks Listed on the IDX for the 2017 – 2021 Period. This study aims to determine the effect of the soundness level of private commercial banks listed on the Indonesia Stock Exchange in the period 2017 - 2021 which is proxied by RGEC (risk profile, good corporate governance, earnings, and capital) on stock returns. This study uses secondary data with a total of 35 observational data. The method used to test the hypothesis is multiple linear regression analysis. The results of the study show that partially and simultaneously risk profile, good corporate governance, earnings, and capital have a positive and significant influence on the stock returns of Bei Private Commercial Banks for the 2017 – 2021 period. Meanwhile, the coefficient of determination shows that 88% of company stock returns are influenced by RGEC (risk profile, good corporate governance, earnings,